Instrumental music and Franciscan liturgy - Venišnik, Vesna (Muzikološki zbornik, 2014)
The Franciscan Library in Novo mesto holds a rather large collection of 18th century sacred and secular music. Among the preserved music there are also several symphonies. The article deals with their characteristics and the possibilities of their performance during the church liturgy.
Keywords: 18.st.; frančiškanski redovi; liturgija; Novo mesto; simfonije; uverture